2013
DOI: 10.18227/1982-8470ragro.v7i2.1235
|View full text |Cite
|
Sign up to set email alerts
|

Adaptabilidade e estabilidade de genótipos de soja em Tocantins.

Abstract: Resumo -Objetivou-se com este trabalho estudar a estabilidade fenotípica de cultivares de soja, quanto à produção de grãos, em oito ensaios, quatro na cidade de Gurupi-TO e, quatro na cidade de Palmas -TO, conduzidos durante os anos de 2008 a 2012. Os ensaios foram instalados com delineamento em blocos casualizados, com quatro repetições, e onze cultivares de soja. Foram utilizadas as metodologias de análise de estabilidade de Eberhart e Russell (1966), Lin e Binns (1988) modificado por Carneiro (1998), e Anni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 5 publications
2
10
0
4
Order By: Relevance
“…Barros et al (2009) found similar results in a study with 29 genotypes in six environments, with all pairs of environments presenting complex interactions. In a study with 11 cultivars, in eight environments in the State of Tocantins (Brazil), Carvalho et al (2013) showed complex interactions in terms of productivity among all the pairs of environments.…”
Section: Resultsmentioning
confidence: 99%
“…Barros et al (2009) found similar results in a study with 29 genotypes in six environments, with all pairs of environments presenting complex interactions. In a study with 11 cultivars, in eight environments in the State of Tocantins (Brazil), Carvalho et al (2013) showed complex interactions in terms of productivity among all the pairs of environments.…”
Section: Resultsmentioning
confidence: 99%
“…A cultura do milho responde à interação dos diversos fatores climáticos, sendo os de maior influência sobre a cultura a radiação solar, a precipitação e a temperatura, que atuam nas diferentes atividades fisiológicas da planta (Landau et al, 2009). Carvalho et al (2013) ao estudarem o efeito da estratificação e dissimilaridade ambiental em genótipos de milho no Estado do Tocantins, usando manejo de adubação e safra como fatores de diferenciação dos ambientes, verificaram que o manejo da adubação e a safra foram eficazes em proporcionar condições distintas de desenvolvimento dos genótipos.…”
Section: Tableunclassified
“…For Eberhart and Russel (1966) the ideal genotype is the one with high productivity, R 2 equal to unity, and non-significant. For this aspect, the ideal genotypes were TMG 801, UFUS 1117-01, UFUS 1117-07 and UFUS 1117-08 (Table 3), as they presented above-average productivity, 2284.13 kg ha -1 (Table 4), were able to respond satisfactorily to the improvement of the environment and presented high productive capacity in favorable and unfavorable environments (CARVALHO et al, 2013).…”
Section: Resultsmentioning
confidence: 99%